Journalists’ perceptions of the use of Artificial Intelligence (AI) platforms in news production: A case study of Harian Disway Online Media - Mohamad Nur Khotib; Bayu Wira Handyan (Priviet Social Sciences Journal, 2026)
This study examines journalists’ perceptions of the use of artificial intelligence (AI) in the news production process at Harian Disway, a digital-native media outlet based in Surabaya. Employing a descriptive qualitative approach through in-depth interviews, participant observation, and document analysis, the study explores how journalists interpret, utilize, and evaluate AI within newsroom practices. The findings indicate that AI is primarily used as a technical assistant, particularly for translation, editing, and content optimization, rather than as a substitute for journalistic creative work. Journalists emphasize the necessity of human control because of AI’s limitations in factual accuracy and contextual understanding. Ethical concerns also emerge, particularly regarding excessive dependency on AI and the potential erosion of writing skills, particularly in feature writing. Drawing on Diffusion of Innovations Theory and Social Perception Theory, this study demonstrates that AI adoption at Harian Disway is selective, pragmatic, and firmly embedded within the framework of editorial ethics.